MENGKAIS KEBAIKAN DENGAN BERBAGAI BENTUK KOMPETISI MENUJU KERIDHAAN ALLAH - Rusdiah Rusdiah (Jurnal Ilmiah Ilmu Pendidikan dan Kedakwahan, 2023)
Competing in goodness is included in worship if it is intended positively which will have a good impact on oneself. Therefore, competing in goodness is tantamount to gaining rewards towards Allah's pleasure. Even more so if you do it according to Allah's commands, such as doing good to your fellow believers, loving orphans, or carrying out the obligatory worship and His sunnah. At this time, it is rare for people to compete in goodness. Usually when they compete, they justify any means to bring down their opponents. Therefore, this material is very important for us to discuss, so that in the future people can realize that competing must also follow God's rules, so that it is beneficial for the perpetrators. In this case it really needs to be studied about competing in goodness, the arguments that explain about competing in goodness, and various forms of competing in goodness in everyday life in achieving God's pleasure.